(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Diabetic wound healing remains a major clinical challenge due to prolonged inflammation, oxidative stress, impaired angiogenesis, and increased susceptibility to infection. Ferulic acid (FA) possesses potent antioxidant and anti-inflammatory properties; however, its poor aqueous solubility limits its therapeutic effectiveness. This study aimed to develop a lemongrass essential oil-based ferulic acid-loaded nanoemulgel (DLMGO-G) to enhance topical drug delivery and accelerate diabetic wound healing. The nanoemulgel was prepared using the phase inversion composition technique and characterized for particle size, morphology, drug release, and stability. In vitro studies using L929 fibroblast cells evaluated cytotoxicity, cellular uptake, reactive oxygen species (ROS) generation, apoptosis, and wound migration. The wound healing efficacy was further assessed in streptozotocin-induced diabetic rats through wound contraction, histopathological examination, oxidative stress markers, inflammatory cytokines, and MMP-9 estimation. The optimized nanoemulgel exhibited nanosized droplets with uniform morphology, sustained drug release, enhanced antioxidant activity, improved cellular uptake, and reduced cytotoxicity. In vivo results demonstrated significantly faster wound contraction, decreased oxidative stress, reduced pro-inflammatory cytokines and MMP-9 levels, increased anti-inflammatory IL-10, and enhanced collagen deposition compared with the diabetic control group. These findings indicate that ferulic acid-loaded nanoemulgel is a promising topical therapeutic system for improving diabetic wound healing through its antioxidant, anti - inflammatory, and tissue regenerative properties.